2009
DOI: 10.3144/expresspolymlett.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based acoustic emission characterization of damage mechanism in composite materials under mode I delamination at different interfaces

Abstract: Abstract. In this paper, acoustic emission (AE) monitoring with a wavelet-based signal processing technique is developed to detect the damage types during mode I delamination on glass/polyester composite materials. Two types of specimen at different midplane layups, woven/woven (T3) and unidirectional/unidirectional (T5), leading to different levels of damage evolution, were studied. Double cantilever beam (DCB) is applied to simulate delamination process for all specimens. Firstly, the obtained AE signals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Wavelet transform has been used by several researchers in studying the relationship between AE signals and damage modes. [19][20][21] The results of these studies indicate that frequency analysis is an effective way for processing AE signals of composite materials.…”
Section: Introductionmentioning
confidence: 95%
“…Wavelet transform has been used by several researchers in studying the relationship between AE signals and damage modes. [19][20][21] The results of these studies indicate that frequency analysis is an effective way for processing AE signals of composite materials.…”
Section: Introductionmentioning
confidence: 95%
“…Some advantages of AE method are online failure inspection, recognition and classification of damage mechanisms in real time [3][4][5][6][7][8]. Acoustic Emission (AE) is a robust nondestructive method for detection and recognition of different damage modes in composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…For this particular purpose, continuous wavelet transform (CWT) provides better accuracy for both time and frequency information compared with the short-time Fourier transform (STFT) method (Daubechies, 1990). Several researchers interested in MAE have successfully used wavelet analysis, either for source location (Jiao et al, 2004;Jiao et al, 2006;Jiao et al, 2008;Oskouei et al, 2009;Hamstad et al, 2002) or for failure characterization (Ni & Iwamoto, 2002;Marec et al, 2008). However, Hafizi et al (2012) have shown the suitability of source mapping using STFT in their work.…”
Section: Modal Acoustic Emissionmentioning
confidence: 99%